Designing of PLA scaffolds for bone tissue replacement fabricated by ordinary commercial 3D printer - Gregor, Aleš; Filová, Eva; Novák, Martin; Kronek, Jakub; Chlup, Hynek; Buzgo, Matěj; Blahnová, Veronika; Lukášová, Věra; Bartoš, Martin; Nečas, Alois; Hošek, Jan (Journal of biological engineering, 2017)
BACKGROUND: The primary objective of Tissue engineering is a regeneration or replacement of tissues or organs damaged by disease, injury, or congenital anomalies. At present, Tissue engineering repairs damaged tissues and organs with artificial supporting structures called scaffolds. These are used for attachment and subsequent growth of appropriate cells. During the cell growth gradual biodegradation of the scaffold occurs and the final product is a new tissue with the desired shape and properties. In recent years, research workplaces are focused on developing scaffold by bio-fabrication techniques to achieve fast, precise and cheap automatic manufacturing of these structures. Most promising techniques seem to be Rapid prototyping due to its high level of precision and controlling. However, this technique is still to solve various issues before it is easily used for scaffold fabrication. In this article we tested printing of clinically applicable scaffolds with use of commercially available devices and materials. Research presented in this article is in general focused on "scaffolding" on a field of bone tissue replacement. RESULTS: Commercially available 3D printer and Polylactic acid were used to create originally designed and possibly suitable scaffold structures for bone tissue engineering. We tested printing of scaffolds with different geometrical structures. Based on the osteosarcoma cells proliferation experiment and mechanical testing of designed scaffold samples, it will be stated that it is likely not necessary to keep the recommended porosity of the scaffold for bone tissue replacement at about 90%, and it will also be clarified why this fact eliminates mechanical properties issue. Moreover, it is demonstrated that the size of an individual pore could be double the size of the recommended range between 0.2-0.35 mm without affecting the cell proliferation. CONCLUSION: Rapid prototyping technique based on Fused deposition modelling was used for the fabrication of designed scaffold structures. All the experiments were performed in order to show how to possibly solve certain limitations and issues that are currently reported by research workplaces on the field of scaffold bio-fabrication. These results should provide new valuable knowledge for further research.
Keywords: Rapid prototyping; Rebel II; Tissue engineering; Scaffold; Fused deposition modelling; Bio-fabrication; Polylactic acid; 3D printing